Retraction notice: Effect of educational interventions on health in childhood: a meta-analysis of randomized controlled trials [Public Health Volume 164, November 2018, Pages 134-147]. (December 2021) - Wang, X.; Zhou, G.; Zeng, J.; Yang, T.; Chen, J.; Li, T.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal ). The article is a duplicate of a paper that has already been published in Medicine, 97 (2018) e11849 https://doi.org/10.1097/MD.0000000000011849 . Redundant publications overweigh the relative importance of published findings and distort the academic record of the authors. One of the conditions of submission of a paper for publication is therefore that authors declare explicitly that the paper has not been previously published and is not under consideration for publication elsewhere. As such this article represents a misuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.